Inadequate detection of the FSHR complicates future research on extragonadal FSHR localization - Tedjawirja, Victoria N.; Hooijer, Gerrit K. J.; Savci-Heijink, C. Dilara; Kovac, Kristina; Balm, Ron; de Waard, Vivian (Frontiers in Endocrinology, 2023)
Recently, follicle stimulating hormone (FSH) through interaction with its receptor (FSHR) has been proposed to play a role in postmenopausal osteoporosis and cardiovascular disease, rather than the loss of estrogen. To explore this hypothesis, unravelling which cells express extragonadal FSHR on protein level is key. In this light, we used two commercial anti-FSHR antibodies and validated them by performing immunohistochemistry on positive (ovary, testis) and negative controls (skin). However, the monoclonal anti-FSHR antibody could not identify the FSHR in ovary or testis. The polyclonal anti-FSHR antibody stained the granulosa cells (ovary) and Sertoli cells (testis), yet there was equally intense staining of other cells/extracellular matrix. Furthermore, the polyclonal anti-FSHR antibody also stained skin tissue extensively, suggesting that the antibody stains more than just FSHR. These findings may add accuracy to literature on extragonadal FSHR localization and warrants attention to the use of inadequate anti-FSHR antibodies to value the potential role of FSH/FSHR in postmenopausal disease.